Process SOAP with VTD-XML discover the benefits. - Zhang, Jimmy
SOAP is an XML based data protocol standardized by W3C for the purpose of enabling inter-application data exchange over the Internet. In a typical Web Services scenario, a SOAP message delivered via HTTP needs to be parsed before anything else can happen. As two popular SOAP processing methods, DOM and SAX/Pull force application developers to choose between performance/memory efficiency and ease of use. VTD-XML is the latest open-source, "non-extractive" XML processing API written in Java that overcomes many problems and issues of the status quo. The combination of its high performance, low memory footprint, random access, incremental update and inherent persistence simply means this: With VTD-XML, application developers can finally unleash to the fullest extent the power of SOAP.